Anxiety as a Syndrome of Modern Social-Cultural Crisis - Gharagulyan, Arman (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The article examines anxiety as a socio-cultural phenomenon and a consequence of modern lifestyle. The modern individualized society with its paradigms of “social competition” and “luck” is the strongest source of loneliness, alienation, and anxiety. The general civilization problem of anxiety in modern post-Soviet societies, due to its economic, political and spiritual characteristics, acquires new facets, adversely affecting people’s self-awareness and the processes of democratization of society.
Keywords: anxiety, fear, alienation, loneliness, luck, social competition, individualized society, authoritarianism, democracy